Understanding the Ghanaian Telecom Reform: An Institutional Theory Perspective - Peter Tobbin (International Telecommunications Society (ITS), 2010)
Telecommunication reform, regulation and policies of various countries have been a subject of intense debate and analysis over the last decade or two. Almost all countries have embarked on some type of telecommunication reform with varied degrees of success and failures. Traditionally, the reason for the reform is solely placed on the inefficiencies of the incumbent national telecom provider. By applying the normative, rational?choice, historical and cultural-cognitive approaches in institutional theory, this study seeks to further explain the key factors that led to the Ghanaian telecom reform. And to assess the various exogenous and endogenous factors that interplayed to bring about the reform. And how various actors reacted to the institutional changes involved in the reform process. A combination of review of secondary data and empirical data from interviews were used in the analysis. The product of this study was a description of the reason and effect of this phenomenal institutional change on the telecommunication industry of Ghana.
Keywords: 330